ANALISIS PENGARUH TRANSPARANSI, AKUNTABILITAS DAN PARTISIPASI MASYARAKAT TERHADAP PENGELOLAAN ALOKASI DANA DESA - Aditya, Wahyu; Widaryanti, Widaryanti (STIE PENA, 2022)
This study aims to analyze the effect of Transparency, Accountability, and Community Participation on Village Fund Allocation. The independent variables used in this study are Transparency, Accountability, and Community Participation. The dependent variable in this study is the Village Fund Allocation Management. In this study, primary data was used from the distribution of questionnaires. The population in this study are people who are in the Kaloran sub-district. The sampling technique used is purposive sampling and the number of samples is 172 questionnaires. The data analysis method used the SPSS 26 program. The results of this study indicate that transparency has a positive effect on the management of village fund allocations. Accountability has a positive effect on the Management of Village Fund Allocation. Community participation has a positive effect on the Management of Village Fund Allocation.Keywords: Transparency, Accountability, Community Participation, Village Fund Allocation Management.